خصوصية الركن المادي لجرائم تسيير شركات المساهمة في التشريع الجزائري - جحنيط, خديجة; حداد, عيسى (University of Eloued جامعة الوادي, 2020)
تركز هذه الدراسة على إبراز خصوصية الركن المادي لمختلف النصوص التجريمية لأعمال تسيير شركات المساهمة إذ بتطبيق العناصر المكونة له على هذه الجرائم،وجدنا أن المشرع الجزائري قد اعتبر السلوك السلبي القاعدة العامة في هذه الجرائم بينما السلوك الإيجابي فأصبح يعد استثناء فيها، كما رفع من درجة التجريم لما جعل من الخطر الذي يهدد بالمصلحة المحمية للشركة القاعدة العامة للتجريم أما جرائم الضرر اعتبرت استثناء فيها. غير أن تشعب هذه النصوص الجزائية حال دون تحديد الجرائم وحصرها بدقة حتى يتسنى لنا ضبط خصوصية الركن المادي في هذه الجرائم ،مما يستوجب على المشرع مسايرة هذه الخصوصية و الذاتية للركن المادي المكون لهذه الجرائم بسن تشريعات تتناسب و طبيعتها. The study aims to demonstrate the specificity of the material element in the legal texts that determine crimes in the management of joint-stock companies. By applying the components of the material element on these crimes, the study finds out that the Algerian legislator considered the negative behavior to be a general rule, while positive behavior becomes an exception in these crimes. Moreover, he increases the degree of criminalization when he considers the danger that threatens the protected interest of the company to be the general rule of criminalization, whereas the damage crimes are considered as an exception. Nevertheless, due to the complexity of these penal texts, the crimes have not been specified accurately in order to set the privacy of the material element. This makes it necessary for the legislator to keep pace with the specificity of this material element by enacting legislation appropriate to its nature.
مجلد11، عدد3
Keywords: الركن المادي ؛جرائم التسيير؛ شركات المساهمة ؛ السلوك السلبي؛السلوك الإيجابي؛جرائم الخطر؛جرائم الضرر.; Material element , Management crimes, Join-stock companies , Negative behavior, Positive behavior, Risk crimes, Damage crimes